An alternative approach to primary rhinoplasty using Walsham forceps. Issue 11 (November 2014) - Bowles, P F D; Fu, B; Cartwright, S J; Watts, S J
Abstract Background: The successful execution of lateral osteotomies in rhinoplasty is an important step that can influence the functional and aesthetic outcome of the procedure. Objective: This paper describes an alternative method for achieving mobilisation of the nasal bones by careful application of Walsham forceps during primary rhinoplasty.